As transformações da feira Ana Primavesi, em Santa Maria/RS, em decorrência da pandemia do SARS-CoV-2 (Covid-19) - Souza, Alessandra (2023)
The SARS-CoV-2 (COVID-19) pandemic has affected the functioning of several marketing models in Brazil and worldwide. According to the Brazilian Institute of Geography (IBGE), of the 3.2 million companies operating in the first half of August 2020, 38.6% indicated that the pandemic significantly affected their results. One of the marketing models affected by the pandemic was the Ana Primavesi Fair, which is an organic fair that sells agroecological products. Faced with this new reality, it was asked: What were the changes that occurred in the relations between farmers and consumers of the Ana Primavesi Fair, resulting from the SARSCoV-2 (COVID-19) pandemic. It was possible to identify in the speech of farmers and consumers that there were changes in the fair, such as: change of location, concern with sanitary measures and distancing of people inside the fair. The dynamics between farmer and consumer were understood as positive, because the relations were closer between them. The differences between conventional and organic agriculture were analyzed, and the contrast between both was observed. The difficulties of farmers during the pandemic period have been identified in a variety of ways, such as the change of the market location and the fear of consumers going to the fair at the beginning of the pandemic. It was possible to understand the new relationships between farmer and consumer, because several customers knew the fair through social networks.